How inventor royalty shares affect patenting and income in Portugal and Spain - Arqué-Castells, Pere (2015)
Portuguese and Spanish universities have adopted well-defined royalty sharing schedules during the last fifteen years. We investigate whether these inventor royalty shares have been effective at stimulating inventors’ efforts and ultimately improving university outcomes. We base our empirical analysis on university-level data as well as on new self-collected surveys completed by inventors and Technology Transfer Offices (TTOs). Econometric evidence from the university-level dataset indicates that royalty shares have no impact on patenting or licensing income. The same result emerges from the inventors’ survey, with most respondents claiming to be largely unaffected by royalty sharing. Evidence from both the TTO and inventors’ surveys suggests that inventors do not react to royalty sharing because of the poor commercial prospects of their inventions, which means there is little income to be shared. These poor prospects appear to reflect the fact that the TTOs do not focus sufficiently on commercializing inventions and inventors are unable to produce potentially licensable inventions.